Factors Influencing Cognitive Academic Language Proficiency in Academic Speaking among EFL Pre-Service Teachers - Reynaldi Karim; Muziatun; Haris Danial (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study addresses the limited empirical attention to Cognitive Academic Language Proficiency (CALP)-oriented speaking in Indonesian EFL teacher education, where previous studies often examine speaking anxiety, teaching strategies, and oral communication separately. It explores the factors influencing students’ CALP in academic speaking at the English Language Education Study Program (ELESP), Universitas Negeri Gorontalo. A qualitative descriptive design was employed with twelve sixth-semester pre-service English teachers who had taken the Speaking for Academic Purposes course. Data were collected through semi-structured interviews, classroom observations, and documentation analysis, and were analyzed thematically. The findings reveal four interconnected factors: language exposure, teaching practices, affective factors, and linguistic knowledge. Limited exposure to academic English reduced students’ familiarity with formal vocabulary, academic expressions, and discourse organization. Teaching practices such as English-only activities, debates, presentations, lecturer modeling, correction, and feedback provided structured opportunities for academic speaking practice. Affective factors, particularly anxiety, fear of mistakes, and lack of confidence, reduced spontaneous participation. Linguistic knowledge emerged as the dominant constraint because limited academic vocabulary, grammar mastery, and discourse organization restricted students’ ability to formulate arguments and answer questions, while also intensifying anxiety. Pedagogically, the findings imply that academic speaking instruction should integrate explicit academic vocabulary, discourse organization, critical response strategies, constructive feedback, and emotionally supportive practice.